INTEGRATION OF LOCAL WISDOM IN ENDE LIO IKAT WEAVING INTO CREATIVE ECONOMICS LEARNING MEDIA - Stefanus H. Gusti Ma; Ana Maria Gadi Djou; Marsel Nande; Helena Rosalia Parera; Sayful Amrin (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Ende Lio ikat weaving is a cultural heritage of East Nusa Tenggara that is rich in philosophical values and creative economic potential. Yet, the younger generation's knowledge of this local wisdom is increasingly fading. This activity aims to integrate the local wisdom of Ende Lio ikat weaving into creative economy learning media at Tri Dharma Ende Junior High School, thereby enhancing students' understanding of creative economic potential based on local culture, while preserving the ikat weaving cultural heritage that serves as the identity of the Ende community in East Nusa Tenggara. The implementation methods include: 1) Field observation, conducted to carry out initial coordination with Tri Dharma Private Junior High School to discuss the technical implementation of the activity. 2) Development of learning media on ikat weaving economic activities covering production, distribution, and consumption. 3) Classroom implementation, which involves conducting lessons in grade VII using the prepared media. Through a contextual learning approach, students are introduced to local wisdom values, the production process, and strategies for developing ikat weaving products as creative economy commodities. The results of the activity demonstrate an increase in students' understanding of the cultural values of Ende Lio ikat weaving and broaden their entrepreneurial insights based on local potential that can be applied in the future.